The The Relationship Between Upper Arm Circumference of Pregnant Women and Birth Weight - Zahariah, Sultanah; Putri, Herlidian (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Upper Arm Circumference is an anthropometry that can describe the nutritional status of pregnant women and to determine the risk of chronic energy deficiency or malnutrition. Birth weight is an indicator of neonate health, birth weight is influenced by the nutritional status of pregnant women. The design of this study was an analytic survey, with a Case Control (Retrospective) approach. The study was conducted at the Jenggawah Health Center, Jember Regency, January-March 2024. The population in this study were mothers who were recorded to have given birth in the Jenggawah Public Health Center Working Area of Jember Regency in January - February 2024, which amounted to 41 populations. Total sampling. The research instrument used a check list sheet using secondary data. Bivariate data analysis using spearman rank test. The test results obtained a significance value or p value of 0.017 below the α value (0.05) which means that there is a relationship between the size of the arm circumference of pregnant women with the baby's birth weight. The result of the correlation coefficient value of 0.371 which means that the level of relationship in the category is sufficient.